Critical Bodies
XII, 206 p.
Keywords: Using work produced from the critical and postmodern arena in social sciences, this book examines three key areas - representation, identities and practice - to explore and interrogate how body and weight management, subjectivities, experiences and practices are constituted within and by the normative discourses of contemporary western culture.